2013
DOI: 10.2503/jjshs1.82.283
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Floral Induction in Citrus

Abstract: In the citrus industry, juvenility and alternate bearing are serious problems that cause lengthening of the breeding cycle and instability of annual fruit production, respectively. Both phenomena are closely related to flowering behavior: juvenility is caused by suppression of flowering in young plants and alternate bearing mainly results from suppression of flowering by fruit production. Many researchers have conducted studies into citrus flowering in a quest to resolve these problems. In recent years, molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 64 publications
2
27
0
3
Order By: Relevance
“…2A, B, see all markers without distinction). As we previously reported (Nishikawa, 2013;Nishikawa et al, 2012Nishikawa et al, , 2016, trees with low CiFT mRNA levels in November bore few flowers the following spring, while trees in which CiFT was highly expressed produced more flowers. The relationship between CiFT mRNA level and number of flowers per 100 nodes showed an exponential pattern.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…2A, B, see all markers without distinction). As we previously reported (Nishikawa, 2013;Nishikawa et al, 2012Nishikawa et al, , 2016, trees with low CiFT mRNA levels in November bore few flowers the following spring, while trees in which CiFT was highly expressed produced more flowers. The relationship between CiFT mRNA level and number of flowers per 100 nodes showed an exponential pattern.…”
Section: Resultssupporting
confidence: 70%
“…Fruit production is also a factor that suppresses floral induction. In citrus trees, CiFT expression levels in the fall and winter are negatively correlated with the number of fruits produced, but positively correlated with the number of flowers the following spring (Nishikawa, 2013;Nishikawa et al, 2012Nishikawa et al, , 2016. Furthermore, CiFT expression and floral induction are enhanced by drought stress (Chica and Alberigo, 2013), and suppressed by gibberellin treatment (GoldbergMoeller et al, 2013;Muñoz-Fambuena et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been indicated that citrus FLOWERING LOCUS T (CiFT) plays an important role in the flowering of citrus and that fruit bearing suppresses floral induction via the suppression of CiFT expression (Nishikawa, 2013;Nishikawa et al, 2007Nishikawa et al, , 2012. In recent years, transcriptomic and proteomic analyses have been conducted regarding alternate bearing in citrus (Muñoz-Fambuena et al, 2013a, b;Shalom et al, 2012Shalom et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%